Limited Salt Tolerance of Indonesian Rice Varieties Biosalin-1-Agritan and Biosalin-2-Agritan at Early Seedling Stage under NaCl Stress - Herwibawa, Bagus; Kusmiyati, Florentina; Arafat, Septrial; Irawan, Albertus Fajar; Anasrullah, Anasrullah (Trends in Sciences, 2025)
This study evaluated the salt tolerance of 2 salt tolerant rice varieties, Biosalin-1-Agritan and Biosalin-2-Agritan under NaCl concentrations ranging from 0 to 50 part-per-thousand (ppt) to assess their potential for large-scale cultivation on saline soils. Plant height, root length, fresh weight and dry weight were measured at 5 and 12 days after NaCl exposure, indicating both varieties maintained stable growth at NaCl levels up to 10 ppt, but growth metrics declined significantly at higher salinity levels. Notably, Biosalin-2-Agritan showed marginally better tolerance than Biosalin-1-Agritan, with resilience in some growth traits. Despite these observations, the limited resilience of both varieties under high salinity suggests that further genetic improvements, such as sodium azide-induced mutagenesis, are necessary to enhance their performance. This study provides essential insights into the salt tolerance of these rice varieties, supporting ongoing efforts to expand agricultural productivity in saline environments and strengthen food security in Indonesia. HIGHLIGHTS Limitations of Indonesian salt-tolerant rice varieties. Phenotypic differences in growth responses to NaCl stress. Impact of extreme salinity levels on rice growth at early seedling stage. GRAPHICAL ABSTRACT